KOMUNITAS ORANG SUNDA DI DESA SERESAM KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU - Junita "; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Sundanese community was able to maintain Sisingan and Jaipong in Seresan village, Seberida Indragiri Hulu regency. Sisingan and Jaipong as a traditional art are used to entertain the society and also often held in Seresam village. The aim of set up Sisingan and Jaipong is not only as an entertainment but also as tightness of relationship between communities and other Sundanese ethnics. This research used descriptive qualitative method. It is a kind of research that see about situation, interpret and then describe the condition of object phenomena that happened in the society. The data sources were primary and secondary data. The primary data is needed through interview while secondary data is collected from books, internet and other documents that are related. The sample in this research was six participant that are incorporated in Sundanese community in Seresam village, Seberida, Indragiri Hulu regency whose include organizers and members. The sample taking technique used purposive sampling. Based on the result finding sundanese community in maintaining Sisingan Jaipong arts have supplementary and inhibitor factor. The supplementary factor is the availability of facilities, togetherness and solidarity community members and the participation in maintaining Sisingan and Jaipong. While inhibitor factor is the limited budget and the business of some Sundanese community. Sundanese conformity did not differentiate the differentiation between the local community and Sundanese community. There wasn’t disputes and hostility that happened between local community and Sundanese community, Sisingan and Jaipong also became favorites in every level, among old people, teenagers, and also children.Key Words: community, Sundanese, conformity, Sisingan and Jaipong.